مساهمة نظام المعلومات التسويقي في مواجهة آثار تحرير تجارة الخدمات المصرفية بالبنوك العمومية الجزائرية - دراسة تحليلية وفق المقاربة المعجمية- - محلوس, زكية (جامعة الوادي University of Eloued, 2019)
هدفت الدراسة إلى التعرف على مساهمة نظام المعلومات التسويقي في مواجهة آثار تحرير تجارة الخدمات المصرفية، فقد تم التركيز على متغيرين تابعين هما القدرة التنافسية وإدارة الأزمات في البنوك بهدف مواجهة آثار تحرير تجارة الخدمات المصرفية وهو القدرة التنافسية بأبعادها المتمثلة في جودة الخدمة، توظيف التكنولوجيا، الحصة السوقية والربحية والمتغير التابع الثاني والمتمثل في إدارة الأزمات بمراحلها الثلاثة وهي مرحلة ما قبل الأزمة ومرحلة الأزمة ومرحلة ما بعد الأزمة في البنوك العمومية الجزائرية بهدف مواجهة آثار تحرير تجارة الخدمات المصرفية، و قد اعتمد البحث على المقاربة المعجمية في تحليل البيانات التي تم جمعها من خلال مقابلة مع 6 إطارات من البنوك العمومية الجزائرية ، وتوصلنا من خلال الدراسة إلى عدة نتائج، من أهمها: - أن هناك مساهمة لنظام المعلومات التسويقي في زيادة القدرة التنافسية للبنوك العمومية الجزائرية. - أن هناك مساهمة لنظام المعلومات التسويقي في إدارة الأزمات في البنوك العمومية الجزائرية. This study aimed identifying the contribution of the marketing information system in facing the effects of liberalizing the banking service trade. two variables were focused on competitiveness and crisis management in banks in order to face the effects of liberalizing the trade of banking services. Thus, a special model has been adopted to study of the previous relationship, based on dividing the competitiveness- As the first dependent variable- to the following dimensions: quality of services, technology utilization, profitability, market share , In addition to that, the crisis management- the second dependent variable - was divided into pre-crisis phase, Crisis stage and post-crisis phase.In the Algerian public banks to counter the effects of liberalization of banking services. the lexical approach was adopted in the analysis of quantitative data, which was carried out with the six executives from the previous banks. The study concluded at the following results: -That there is a contribution to the system of information marketing in increasing the competitiveness of Algerian public banks. -That there is a contribution to the information system in crisis management in the Algerian public banks.
La contribution du système d'information marketing aux effets de la libéralisation du commerce des services bancaires dans les banques publiques algériennes
مقال
Keywords: نظام معلومات تسويقي، قدرة تنافسية، إدارة الأزمات، بنوك عمومية جزائرية